2008
DOI: 10.1002/anie.200801770
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Organic–Inorganic Polyoxometalates: Functionalization of VIV/VV Nanosized Clusters to Produce Molecular Capsules

John M. Breen,
Wolfgang Schmitt

Abstract: Functionalization of polyoxovanadate clusters using phosphonate and arsonate ligands results in molecular capsules (see structure; green V, purple P, red O, black C). Through the use of extended homologous ligands, these hybrid organic‐inorganic capsules can be successively elongated into tubular molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 143 publications
(71 citation statements)
references
References 50 publications
3
63
0
Order By: Relevance
“…For hybrid organic-inorganic polyoxidometalate frameworks including arylarsonic acid ligands, see: Breen, Clé rac et al (2012) ;; ; Onet et al (2011); Breen & Schmitt (2008 Table 1 Selected bond lengths (Å ). Data collection: SMART (Bruker, 1997); cell refinement: SAINT (Bruker, 1997); data reduction: SAINT; program(s) used to solve structure: SHELXS97 (Sheldrick, 2008) and OLEX2 (Dolomanov et al, 2009); program(s) used to refine structure: SHELXL97 (Sheldrick, 2008) and OLEX2; molecular graphics: OLEX2; software used to prepare material for publication: SHELXL97 and OLEX2.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…For hybrid organic-inorganic polyoxidometalate frameworks including arylarsonic acid ligands, see: Breen, Clé rac et al (2012) ;; ; Onet et al (2011); Breen & Schmitt (2008 Table 1 Selected bond lengths (Å ). Data collection: SMART (Bruker, 1997); cell refinement: SAINT (Bruker, 1997); data reduction: SAINT; program(s) used to solve structure: SHELXS97 (Sheldrick, 2008) and OLEX2 (Dolomanov et al, 2009); program(s) used to refine structure: SHELXL97 (Sheldrick, 2008) and OLEX2; molecular graphics: OLEX2; software used to prepare material for publication: SHELXL97 and OLEX2.…”
Section: Related Literaturementioning
confidence: 99%
“…In the course of our studies on hybrid organic-inorganic polyoxometalate frameworks, including arylarsonic acid ligands (Breen, Clérac et al, 2012;Onet et al, 2011;Breen & Schmitt, 2008), we attempted to prepare tetrabutylammonium hydrogen phenylarsonate [(C 4 H 9 ) 4 N] + [C 6 H 5 AsO 3 H] -as a starting material for synthesis. Unexpectedly, mixing equimolar amounts of tetrabutylammonium hydroxide and phenylarsonic acid in aqueous solution and slow evaporation resulted in crystals with a 2:1 stoichiometry of tetrabutylammonium to phenylarsonic acid.…”
Section: Lukas Reck and Wolfgang Schmitt Commentmentioning
confidence: 99%
“…In particular, Zubieta’s research group has extensively explored the formation of such hybrid POMs [45, 47, 48, 50, 51]. We have reported several capsular arsonate-stabilized polyoxovanadates that incorporate substituted R-phenylarsonate and investigated their 3D assembly [5356]. In such POMs, each arsonate functionality bridges several metal centers and shows a coordination behaviour that is closely comparable to that of the corresponding phosphonate-stabilized POMs [33, 5356].…”
Section: Introductionmentioning
confidence: 99%
“…We have reported several capsular arsonate-stabilized polyoxovanadates that incorporate substituted R-phenylarsonate and investigated their 3D assembly [5356]. In such POMs, each arsonate functionality bridges several metal centers and shows a coordination behaviour that is closely comparable to that of the corresponding phosphonate-stabilized POMs [33, 5356]. Synthetic approaches to Sn- and Pd-based organoarsonate complexes have also been explored under hydro(solvo)thermal conditions [5759].…”
Section: Introductionmentioning
confidence: 99%
“…Metal organoarsonates are expected to display similar structural chemistry to metal phosphonates, but the obviously larger ionic radius of As 5+ (0.335 Å ) compared with P 5+ (0.17 Å ) and the somewhat weaker acidity of organoarsonic acid could lead to some novel architectures with different physical properties (Xie et al, 2010). In contrast with the attention received by metal phosphonates, studies of metal organoarsonates are still scarce and most of the reported metal organoarsonates are polyoxometallates (POMs) based on vanadium (Breen & Schmitt, 2008), molybdenum (Burkholder et al, 2003;Liu et al, 1988;Barkigia et al, 2002) and tungsten (Johnson et al, 2002) with discrete structures, although a handful of one-or twodimensional structures have also been reported (Burkholder et al, 2003;Reddy et al, 2006;Diop et al, 2002). An effective synthetic method for the design of various metal organoarsonates is the introduction of a variety of functional groups ISSN 2053ISSN -2296 # 2015 International Union of Crystallography such as carboxylate, amino or hydroxy groups, to the organoarsonic ligands.…”
Section: Introductionmentioning
confidence: 99%